2015
DOI: 10.1016/j.hemonc.2014.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Gγ-globin promoter −158 (C>T) XmnI polymorphism in patients with homozygous/compound heterozygous beta thalassaemia

Abstract: XmnI polymorphism in homozygous/compound heterozygous BT group is 13%. The most common genotype associated with XmnI polymorphism was IVSI-5/IVSI-5.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 20 publications
0
9
1
Order By: Relevance
“…The latter findings are consistent with earlier reports that the Xmn I SNP is the commonest ameliorating factor in cases with β° mutations but not β + [4, 37]. However, in our study the percentage of TI patients having the Xmn I SNP was low, in consistency with an earlier report from Brazil (9.7%) [38] but inconsistent to previous reports from Iraq (56.8%) [4], Iran (51.9%), [28] Pakistan (23%) [14] and China (26.5%) [39].…”
Section: Discussioncontrasting
confidence: 57%
See 2 more Smart Citations
“…The latter findings are consistent with earlier reports that the Xmn I SNP is the commonest ameliorating factor in cases with β° mutations but not β + [4, 37]. However, in our study the percentage of TI patients having the Xmn I SNP was low, in consistency with an earlier report from Brazil (9.7%) [38] but inconsistent to previous reports from Iraq (56.8%) [4], Iran (51.9%), [28] Pakistan (23%) [14] and China (26.5%) [39].…”
Section: Discussioncontrasting
confidence: 57%
“…Analysis of the Gγ-globin gene Xmn I SNP showed that three patients were homozygous and one patient was heterozygous for this SNP, three of them have the β 0 /β 0 genotype and one has the β 0 /β + (in addition to –α 3.7 / αα) and the effect of this SNP was clearly illustrated by the high levels of HbF in these patients. The role of Gγ-globin gene Xmn I SNP in increasing HbF levels and moderation of thalassemia phenotype is widely known and reported in many earlier studies [4, 14, 35]. The Xmn I polymorphism is one of three major HbF quantitative trait loci (QTLs) responsible for HbF variation, and it leads to a less severe phenotype by increasing γ-chain production, which helps to neutralize unbounded α-chains [15, 36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study in Pakistan reported that a minor allele in the XmnI locus has a frequency of 23-36% [31], whereas this was reported to be 16% [32] and 8% [33] in Indian and Malay populations, respectively. In accordance with the data from the HapMap project (updated 2012), the rs11886868 genotype has a wide distribution that varies in populations throughout the world.…”
Section: Relationship Between Snps Distribution and Clinical Appearancementioning
confidence: 99%
“…Studies on β-thal carriers from Brazil, Northern Pakistan, Turkey, and Hong Kong reported rates of 0.19, 0.16, 0.18, and 0.07, respectively. [ 23 24 25 26 ] These rates may be relevant to the underlying β-thal genotypes in these populations. Although the current study did not include molecular characterization of the underlying β-genotypes, earlier studies have documented that IVS-II-1 (G>A), codon 44 (-G), codon 5 (-CT), IVS-I-1 (G>A), and codon 39 (C>T) are the five most common β-thal mutants in carriers from our region.…”
Section: Discussionmentioning
confidence: 99%